Acute retinal necrosis by cytomegalovirus in an immunocompetent adult: case report and review of the literature. - Tajunisah, I.; Reddy, S.C.; Tan, L.H. (Kluwer (now part of Springer), 2009)
A rare case of acute retinal necrosis caused by cytomegalovirus in an immunocompetent adult, diagnosed by polymerase chain reaction of vitreous aspirate, with good visual outcome after intravitreal and intravenous ganciclovir and oral prednisolone therapy, is reported. A 50-year-old healthy lady presented with redness and diminution of vision in her right eye of 10 days duration. She had anterior chamber inflammation, marked vitritis, and anterior retinal necrosis in the right eye. Blood and other investigations did not reveal any infectious diseases and HIV testing was negative. The retinal lesions and panuveitis resolved with treatment. Two months later she developed retinal detachment which was treated successfully. The best-corrected vision was 6/12 in the right eye. Seven cases of cytomegalovirus ocular infection in immunocompetent healthy adults, reported in the literature, were reviewed. The different presentations of this disease and the importance of suspecting this causative agent are highlighted.